ADDRESSER-ADDRESSEE RELATIONSHIPS IN STRUCTURALSEMIOTIC ANALYSIS OF LITERATURE - Saidova Rayxonoy Abduganievna (Scholar Express Journal, 2021)
The article provides an overview of the structural-semiotic analysis of the literature. At the same time, the addresser-addressee relationship was also mentioned during the analysis and analyzed using examples.
Keywords: Addresser; addressee; society; symbol